The Business Plan for Sentuh Awan Enterprise: Proposing a New Subsidiary of Palm Oil Nursery Industries - Md Nasir, Ardi Yusnar; Omar, Siti Sarah (Research in Management of Technology and Business, 2022)
Sentuh Awan Enterprise is an agricultural-based company, especially in palm oil seedlings production and services. Sentuh Awan Enterprise (SAE) has high customer demand, but the available stock is insufficient to meet their need. This problem has lasted for almost ten years, and now the demand is increasing because the oil palm seed breed sold by the SAE company is a premium breed in the market. With a shortage of stock, customers had to make early bookings, and sometimes, they had to pay an advance to get the supply of palm seeds. The oil palm nursery industry is a high-risk business as it involves high skills to manage at the initial stage from seed until it reaches the maturity age of 12 months. After 12 months, palm oil seeds can be sold. It also takes up to 14 months to ensure the roots become strong when planted in oil palm plantations. To overcome this problem, the company needs a business plan to open another palm oil nursery branch to suffice the stock and meet customer demand, especially from smallholders. SAE companies also need to analyze Political, Economy, Social, and Technology (PEST) and analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) to get an overview and strategies to start a new oil palm nursery project. In order to comply with MPOB regulations, be recognized under the Code of Good Nursery Practice for Oil Palm Nurseries (CoPN), and persuade customers that they produce high-quality palm oil seedlings, palm oil nurseries must also undergo an evaluation by SAE Company and follow the best management practices (BMP) guidelines to get the best results.